COMMUNICATION INSTRUCTIONAL TEACHER IN INSTILLING VALUES MELAYU CULTURE ON PUPIL SMA NEGERI 3 PEKANBARU - Arissya, Giva; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Communication instructional interaction is very important in the communication process of teaching done by teachers in instilling values of Malay culture to students of SMAN 3 Pekanbaru. Through instructional communication can teachers know how to teach the Malay culture to the students, so as to establish the identity of the Malay culture that does not go away and used as guidelines for behavior in daily life - today. The aim of this study is to explain how the method, the media used, and hambtan - communication barriers instructional teachers in instilling values of Malay culture to students of SMAN 3 Pekanbaru.This research method is qualitative method implemented in SMA Negeri 3 Pekanbaru , located on St. Yos Sudarso, Rumbai – Pekanbaru. The informants consists of teachers, students , principal , Vice-principal with purposiv techniques. Data collection techniques using interviews, observation and documentation.These results indicate Communications Instructional Teacher In Instilling Values Malay Culture On Pupil Sma Negeri 3 Pekanbaru use the lecture method at first or in the end of the class session, the method of administration task as homework, and methods of discussion and presentations. These methods are supported by audio media such as tape recorders, visual media such as pictures or props, and audiovisual media such as Infocus. The obtacles in the instructional communication is a psychological barrier that comes from within the student himself, while technical barrier such as lack of media used its functions and limitations of lesson hours Malay culture.Keywords: communication instructional, values melayu culture.